Peran BPN dalam Penyertifikatan Hak Milik Atas Tanah Adat di Kantor Pertanahan Kabupaten Samosir - Lumban Tobing, Ady Hendra; Limbong, Dayat; Isnaini, Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the legal rules, roles and obstacles faced by BPN employees in Samosir district in the implementation of registration of property rights on customary land. This research uses normative legal research. The results of the study indicate that the rule of law for land registration refers to Law no. 5 of 1960 concerning Basic Regulations on Agrarian Principles and Government Regulation Number 24 of 1997 concerning Land Registration. The registration procedure is as follows: 1) Prepare the required documents, 2) Prepare and submit application letters, 3) Pay the application fee, measurement and inspection of the applicant's land, 4) Make announcements through the general daily news with a period of 60 (sixty) days, 5) Issuance of decrees (Kantah, Kanwil, or BPN RI), 6) Bookkeeping of rights and issuance of certificates. Obstacles that arise and are faced in registering land as property rights in Pangururan District are: 1) Unclear customary land boundaries, 2) There are claims from the state or government, 3) Loss of witnesses or historical actors.